Studying the effect of the environmental factor on the participation of pesticides in the surface sediments of the Shatt al-Arab - Taban , Israa A.; Al-Hejuje, Makia; Al-Saad , Hamed T. (Mesopotamian Journal of Marine Sciences, 2024)
Six stations (Qurna, Al-Diyar, Karma Ali, Al-Ashar, Abi Al-Khasib, and Al-Faw) were chosen along the Shatt Al-Arab, and sediment samples were collected from them on a quarterly basis for the period extending from August 2020 to March 2021 to determine the concentrations of pesticides in them, and some physical and chemical variables (air temperature) were measured. Water, pH, dissolved oxygen, and electrical conductivity (in the water), and the total organic carbon (TOC%) of sediments and sediment tissues were determined. Six stations (Qurna, Al-Deir, Karma Ali, Al-Ashar, Abi Al-Khasib, and Al-Faw) were chosen along the Shatt Al-Arab, and sediment samples were collected from them on a quarterly basis for the period extending from August 2020 to March 2021 to determine the concentrations of pesticides in them, and some physical and chemical variables (air temperature) were measured. Water, pH, dissolved oxygen, and electrical conductivity (in the water), and the total organic carbon (TOC%) of sediments and sediment tissues were determined.The results showed that the range of variables for Shatt al-Arab water is: air temperature (18-43) °C, water temperature (14-34) °C, pH (7-8.52), electrical conductivity (1.29-2.82) mSiemens/cm, Dissolved oxygen (-3.9 11) mg/L and total organic carbon in sediments (22.55-6.17)%.Thirteen compounds representing pesticides were identified, and their concentrations ranged between (0-9.6) micrograms/kg. The highest concentration was due to the Endrin compound, and the lowest concentration (0) micrograms/kg was to the Endosulfan compound. In general, the concentrations were within the internationally permissible limits.